The effect of brand personality on sport team identification - Bayrakdaroglu, Y. (International Journal of Applied Exercise Physiology, 2020)
This study examined the perception levels of brand personalities and team identification of Gümüshanespor spectators, and also analyzed the data in terms of various variables. The participants of this study consisted of a total of 326 spectators (166 female and 160 male) living in the center of Gümüshane, Turkey. As data collection tools Sport Spectator Identification Scale and Brand Personality Scale were used. In the analysis of the data, Single Factor Variance Analysis, Correlation Analysis, and MultipleLinear Regression Analysis were used for variables determined to show normal distribution and homogeneity. On the other hand, Kruskal-Wallis Test was applied to the data that could not provide the parametric test condition. Tukey Test was used in Varianceanalysis, and Mann Whitney U Test was used in the Kruskal-Wallis Test for multiple comparison processes. Findings were obtained in terms of various variables in the analyzes. In addition, the results of the analysis indicated that the brand personality is a significant and powerful predictor of identifying with the team with the sub-dimensions of excitement and sophistication. However, sincerity, competence, and ruggedness variables that make up the brand personality did not make a significant contributionto this predictive model.